2021
DOI: 10.1099/mgen.0.000620
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and emergence of multidrug-resistant Mycobacterium tuberculosis in Chisinau, Moldova

Abstract: The evolution and emergence of drug-resistant tuberculosis (TB) has been studied extensively in some contexts, but the ecological drivers of these two processes remain poorly understood. This study sought to describe the joint evolutionary and epidemiological histories of a novel multidrug-resistant Mycobacterium tuberculosis strain recently identified in the capital city of the Republic of Moldova (MDR Ural/4.2), where gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Our findings are consistent with our earlier work in the Republic of Moldova, which highlighted the presence of highly drug resistant Ural lineage 4.2 strains that appeared to be readily transmitting within the population 13,3638 . However, the R e estimates for Ural 4.2 strains reported here contrast with a recently published study that found that there was a reduced transmission fitness associated with multi-drug resistance in L4 strains in another former Soviet Union country 10 .…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with our earlier work in the Republic of Moldova, which highlighted the presence of highly drug resistant Ural lineage 4.2 strains that appeared to be readily transmitting within the population 13,3638 . However, the R e estimates for Ural 4.2 strains reported here contrast with a recently published study that found that there was a reduced transmission fitness associated with multi-drug resistance in L4 strains in another former Soviet Union country 10 .…”
Section: Discussionsupporting
confidence: 93%
“…Molecular epidemiological studies have shown that TB caused by the spread of TB strains may account for 35 to 40% (even as high as 70%) of TB cases ( 10 ). Increasing evidence shows that the spread of drug-resistant TB strains is an important driving factor for the epidemic of TB ( 11 , 12 ). In view of the transmission of MTB, previous studies have mostly focused on economically developed areas such as Shanghai and Shenzhen, where 73 and 25.2% of MDR patients were likely to be transmitted, respectively ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the human T-cell epitopes in Mtb demonstrated conservative roles, there were two codons with three mutations (Ser315Arg and Ser315Thr of katG , and Thr2Ala of esxW ) in the T-cell epitopes under positive selection, exhibiting higher genetic diversity in specific T-cell epitopes. It was reported that esxW Thr2Ala is associated with increased transmissibility in Lineage 2 (2.2.1) Mtb strains ( Holt et al, 2018 ; Brown et al, 2021 ), and katG _S315R and katG _S315T are both highly reliable markers for isoniazid resistance ( World Health Organization, 2021 ). We speculate that Mtb strains bearing katG 315 mutations are beneficial for the pathogen escaping from isoniazid pressure and human T-cell recognition ( Coscolla et al, 2015 ), and the addition of esxW Thr2Ala increases the speed of the spread of isoniazid-resistant Mtb .…”
Section: Discussionmentioning
confidence: 99%